The stroke rate influences performance, technique and core stability during rowing ergometer - Duchene, Y.; Simon, F. R.; Ertel, G. N.; Maciejewski, H.; Gauchard, G. C.; Mornieux, G. (Sports Biomechanics, 2025)
The aim of this study is to determine the effect of stroke rate on performance, technique and core stability during rowing ergometer. Twenty-four high-level rowers performed maximal intensity one-minute bouts at 20, 28 and 34 spm on a RowPerfect3 ergometer. Power at the handle, legs, trunk and arms levels were determined, and core kinematics and neuromuscular activations were measured. The power at the handle was enhanced with a higher stroke rate in the first half of the drive phase due to higher segment`s powers. This resulted in technical changes, as for instance greater mean to peak power ratio at each segment level. The higher trunk power preceded a delayed trunk extension but without significant increase in the erector spinae activation. This underlines the role of the core stability to transfer forces at a higher stroke rate. However, no co-activation parameters between trunk flexors and extensors helped further to understand this force transfer. Rowing at low stroke rate can be a training strategy to work on earlier trunk extension, while maintaining erectors spinae levels of activation. Training at higher stroke rate will induce a rowing technique closer to competition with greater neuromuscular activations, and maximise power production.